ANALYSIS OF DIFFERENTIATED LEARNING STRATEGIES IN INDONESIAN LANGUAGE LEARNING AT ELEMENTARY SCHOOLS - suwandi, ferina putri eri; Rochmiyati, Siti (JPSD (Jurnal Pendidikan Sekolah Dasar), 2024)
The application of the differentiated learning strategy is an adaptation effort in the classroom that aims to increase students’ enthusiasm in the learning process and fulfill their varied learning needs. This research focuses on Indonesian language learning for 4th grade students at SDN Kaliajir, Sleman. Implementing differentiated learning involves adapting content, processes, and learning products to individual student differences. This research uses a qualitative method with a descriptive approach. Data was collected through three main techniques: interviews, observation, and documentation. Research instruments, interview sheets, observation guides and documents, and citation tools supported this data collection. Based on the research data analysis, it can be concluded that several stages must be fulfilled in implementing differentiated Indonesian language learning. These stages include mapping students’ needs through diagnostic assessments, designing differentiated learning plans that suit students’ needs, and evaluating and reflecting on the learning that has been implemented. The application of the differentiated learning model in Indonesian language learning shows a positive impact, reflected in the increase in students’ enthusiasm during the learning process.